Pemanfaatan Serbuk Gergaji Kayu sebagai Inhibitor Korosi Baja ASSAB 760 di Udara - Refi Yeni; Yerimadesi Busmairizal; Desy Kurniawati (Jurnal Periodic Jurusan Kimia UNP, 2012)
Corrosion problems can cause serious harm, either directly or indirectly, such as the age of the building construction to be reduced from the planned time, resulting in reduced toughness, and environmental pollution. One way to slow the rate of corrosion is to use the inhibitor extract sawdust. Extract sawdust containing lignin can form complexes with iron from steel and adsorbed on the steel surface thus blocking contact between the steel with oxygen in the air. This study aims to utilize waste wood sawdust as steel corrosion inhibitors, view optical surfaces steel before and after coated inhibitor and determine the efficiency of the steel corrosion inhibition by extract sawdust. The method used to determine the rate and efficiency of corrosion is the gravimetric method, which is based on a reduction in weight (weight loss) of steel. Steel surface before and after the coated sawdust extracts viewed using a stereo microscope with a magnification of 40 times. The result showed that sawdust can be used as a corrosion inhibitor of steel with optimum efficiency of 65,398%, from optical picture can be seen that the steel surface is not coated sawdust extract rougher than the surface of the coated steel.